Role of Specialized Pro-Resolving Mediators in Neuropathic Pain - Leuti, Alessandro; Fava, Marina; Pellegrini, Niccolò; Maccarrone, Mauro (Frontiers in Pharmacology, 2021)
Inflammation and neuroinflammation are critical in the generation of neuropathic pain that is experienced in chronic diseases. The aberrant inflammation that triggers this pathophysiologic process can be tracked down to an exacerbated immune response, which establishes a vicious cycle and continuously recruits inflammatory cells by inducing chronic tissue damage. Recently, impairment of the cellular and molecular machinery orchestrated by specialized pro- resolving mediators (SPMs) – i.e., endogenous lipids termed resolvins, protectins, maresins and lipoxins that confine the inflammatory cascades during the “resolution of inflammation” - has emerged as a crucial event in the derangement of the inflammatory homeostasis and the onset of chronic inflammation and pain. Indeed, a deviant inflammatory response that is not adequately controlled by the resolution network leads to the overproduction of pro-inflammatory molecules and neuropathic pain. In the last two decades, convincing evidence has demonstrated that SPMs exert potent anti-hyperalgesic effects in a number of pain-associated paradigms of disease, such as arthritis and chemotherapy-induced peripheral neuropathy, as well as in many experimental models of pain like mechanical allodynia, chemical pain, heat hypersensitivity and phase 1 and 2 inflammatory pain. Of note, accumulated evidence supports a synergy between SPMs and other signalling pathways, such as those mediated by transient receptor potential (TRP) channels and those triggered by opioid receptors, suggesting a previously unexpected molecular network at the base of pain perception. Here, we aim at presenting a state-of-the-art view of SPMs, their metabolism and signalling, in the context of cellular and molecular pathways associated to neuropathic pain.